SCREENING FOR ANXIETY AND DEPRESSION IN CHILDREN WITH ASTHMA - PILOT STUDY - Gaikwad, Pratibha Anil; Asgaonkar, Bharati (International Journal of Research -GRANTHAALAYAH, 2025)
BACKGROUND: Bronchial asthma is an important public health problem at the global level. In India, Prevalence of Asthma in children of 6-13 years is 2.3%. Psychological factors may influence the symptoms and management of Asthma in children. Hence, there is a need to assess Anxiety and Depression in children with asthma. AIMS AND OBJECTIVES: To Screen for Anxiety and Depression by using Revised Children Anxiety and Depression (RCAD) scale in Asthmatic children in the age of 6 to 11 years. Objectives: 1) To assess the Anxiety and Depression by using Revised Anxiety and Depression score in children with asthma and in age and sex matched normal healthy children. 2) To assess and compare sex wise distribution and affection in both the groups METHODOLOGY: An Observational, Cross-sectional study was conducted at the Tertiary health care centre of Mumbai, India. All Asthmatic children who participated in the study were recruited from the Paediatric Asthma Clinic. Normal data was taken from Primary and Secondary school children from Mumbai. Total 6o participants from each group (Control and Asthmatic) were taken and interviewed for RCAD Scale. RESULT: Out of 60 Asthmatic children, RCAD score of Anxiety was 15.00%. Total Anxiety and Depression score was 17% and Depression score was 22% in Asthmatic children. Boys were affected more than girls. RCAD score value showed affected in Normal Children too but the percentage was low as compared to asthmatic children. CONCLUSIONS: This study results revealed that Anxiety and Depression is seen more in Children with Asthma as compared to the control Group.